(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The cold-hardiness of eggs of four stored-products moths exposed to low temperatures (next to and below 0°C) was investigated. Laboratory tests were carried out on eggs of different ages (ranging from 6 to 20 h and from 30 to 48 h) kept at +2°C, -2°C, -5°C, -10°C (±0.5°C) and 70 ±10% RH, for 3, 9, 18, 24 and 48 h. Five replicates and five controls (200 eggs) of each group were tested at each cold exposure at different exposure period. At + 2°C, no significant reduction in the hatching of eggs of E. kuehniella was observed after a 48 h exposure, whereas a 80% mortality of eggs of P. interpunctella and more than 95% mortality for the other two species was obtained. Eggs hatching was lower than 5% for all the species except for E. kuehniella (85% hatching) after an 18 h exposure at -2°C. At -5°C, a 3 h exposure is enough for a total inhibition of the hatching of P. interpunctella, whereas a 9 h exposure produced a mortality higher than 90% in E. cautella and C. cephalonica. At -10°C, no hatching was observed in E. cautella and C. cephalonica after a 9 h exposure, whereas a 24 and 48 h exposure produced a mortality respectively of 60% and higher than 95% of E. kuehniella eggs. On the whole significant differences in mortality between mature or immature eggs were not observed. These results show that P. interpunctella is more susceptible to temperatures lower than 0°C, while E. kuehniella is much more tolerant to the cold.